Legal Status and Protection of Corruption Reporters in Bosnia and Herzegovina - Kazić, Ena (Kriminalističke teme, 2018)
Reason(s) for writing and research problem(s): Primary inspiration for this article is based in the fact that the importance of the role of corruption reporters in determination and prevention of corruption, as well as the need for their prevention hadn’t been problematized from experts. Aims of the paper (scientific and/or social): The main aim of this paper is to establish legal status of corruption reporters in Bosnia and Herzegovina and to determine whether their legal status is homogenized in legal system of Bosnia and Herzegovina. Methodology/Design: In this paper comparative and normative scientific methods had been used. Before relevant provisions of positive codes that refer to protection of corruption reporters have been analysed, general legal analysis of corruption reporters issues had been made, international documents that refer to their protection had been presented and briefly, legal regulation of protection of corruption reporters in several countries had been presented. Afterwards, by using normative scientific method, analysis of relevant provisions of codes in force in Bosnia and Herzegovina had been made. Research/paper limitations: Secret nature of files in which had been decided upon protection request, disabled us to analyse these files detailously, so the informations of the state in practice are of descriptive nature. Results/Findings: Analysed international documentsentitle state members to create a code and to provide protection to people who in good will report corruption. Examples from several states show us that there is practice of counties to protect corruption reporter even post festum (when the damage occurs). Related to domestic law, this research shows that there is unharmonized legal regulation of protection of corruption reporters in Bosnia and Herzegovina. While in the level of Bosnia and Herzegovina and in Republic of Srpska this issue had been regulated by special law, it is not object of code regulation in Federation of Bosnia and Herzegovina and Brčko District BH. Furthermore, two codes that had been analysed show disproportionality in content and volume of protection in the same country. State in practice shows low number of cases where the protection to corruption reporters had been allowed. General conclusion: Inequality in legal regulation and volume of protection of corruption reporters in Bosnia and Herzegovina causes legal inequity of its citizens. It is necessary to establish wide protection of people who can report corruption no matter where they work, and to regulate this issue either in state level or in entity level as well but through harmonized codes. Finally, it is important to develop awareness of importance of corruption reporting in its prevention, of possible harmreporters can face with and of conditions, volume and content of their protection. Research/paper validity: This paper shows importance of protection of corruption reporters and difficulties that they are facing with.